Atomistic insight in the flexibility and heat transport properties of the stimuli-responsive metal–organic framework MIL-53(Al) for water-adsorption applications using molecular simulations. (29th October 2020) - Lamaire, Aran; Wieme, Jelle; Hoffman, Alexander E. J.; Van Speybroeck, Veronique
Abstract : Insight into the heat transport and water-adsorption properties of the flexible MIL-53(Al) is obtained using advanced molecular dynamics simulations. Abstract : To exploit the full potential of metal–organic frameworks as solid adsorbents in water-adsorption applications, many challenges remain to be solved. A more fundamental insight into the properties of the host material and the influence that water exerts on them can be obtained by performing molecular simulations. In this work, the prototypical flexible MIL-53(Al) framework is modelled using advanced molecular dynamics simulations. For different water loadings, the presence of water is shown to affect the relative stability of MIL-53(Al), triggering a phase transition from the narrow-pore to the large-pore phase at the highest considered loading. Furthermore, the effect of confinement on the structural organisation of the water molecules is also examined for different pore volumes of MIL-53(Al). For the framework itself, we focus on the thermal conductivity, as this property plays a decisive role in the efficiency of adsorption-based technologies, due to the energy-intensive adsorption and desorption cycles. To this end, the heat transfer characteristics of both phases of MIL-53(Al) are studied, demonstrating a strong directional dependence for the thermal conductivity.